2014
DOI: 10.3354/meps11035
|View full text |Cite
|
Sign up to set email alerts
|

Trophic role of large benthic sulfur bacteria in mangrove sediment

Abstract: International audienceLarge filamentous sulfur-oxidizing bacteria belonging to the Beggiatoacae family can cover large portions of shallow marine sediments surrounding mangroves in Guadeloupe (French West Indies). In order to assess the importance of Beggiatoa mats as an infaunal food source, observations were conducted of the area within mats and at increasing distances from mats. We used natural isotopic compositions and a C-13 enrichment study. Both revealed an ingestion of bacterial mats by associated meio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…On the contrary, the cosmopolitan gnathostomulid species Haplognathia ruberrima was found in sulphur bacterial mats in Guadeloupe mangroves with δ 13 C values lower than the available measured food sources of this environment. Since no sulphur-oxidising symbionts were observed, it was suggested that the species was grazing selectively and exclusively on the free-living, sulphur-oxidising bacteria (Pascal et al 2014).…”
Section: Adaptation Of Meiofauna To Mangrove Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, the cosmopolitan gnathostomulid species Haplognathia ruberrima was found in sulphur bacterial mats in Guadeloupe mangroves with δ 13 C values lower than the available measured food sources of this environment. Since no sulphur-oxidising symbionts were observed, it was suggested that the species was grazing selectively and exclusively on the free-living, sulphur-oxidising bacteria (Pascal et al 2014).…”
Section: Adaptation Of Meiofauna To Mangrove Conditionsmentioning
confidence: 99%
“…Kito and Aryuthaka (2006) described a new species of the mouthless genus Parastomonema collected in muddy sediments of a mangrove forest in Samut Songkhram, Thailand. Pascal et al (2014) studied the endofauna of bacterial mats between mangrove tree roots and found no differences in abundance with surrounding mangrove, suggesting that this chemosynthetic food source had a limited impact on the structure of the mangrove food web. Both natural isotopic compositions and a 13 C enrichment study demonstrated the uptake of bacterial mats only by associated meiofauna, mainly by rotifers and, to a lesser degree, by small polychaetes and nematodes, and not by the macrofauna (Pascal et al 2014).…”
Section: Adaptation Of Meiofauna To Mangrove Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haplognathia ruberrima had the lowest δ 13 C value of all of the meiofaunal grazers studied in the area: nematode, copepod, turbellarian, rotiferan (Pascal et al . ) and consequently appears to be the only local grazer with this specialized diet. Gnathostomulid abundances are higher at the discontinuity layer between the aerobic surface and the anaerobic sediment and the redox potential discontinuity layer is a site of high bacterial activity involving sulfide oxidation and sulfate reduction (Riedl ; Reise ).…”
Section: Resultsmentioning
confidence: 99%
“…In temperate shallow waters, observations reveal ingestion of filamentous sulfur bacteria by nematode (Bernard and Fenchel, 1995). A trophic role of these bacteria has also been demonstrated in a Caribbean mangrove, in which comparisons of the isotopic composition in natural conditions and after artificial enrichment revealed that sulfur bacteria were ingested by the meiofauna (Pascal et al, 2014).…”
Section: Introductionmentioning
confidence: 86%